Sorghum (Sorghum bicolor) research in India - RANA, B S; SINGH, B H; RAO, M H; INDIRA, S; RAO, S S; KAUL, S L (The Indian Journal of Agricultural Sciences, 2013)
Sorghum [Sorghum bicolor(L.) Moench] research significantly contributed towards the Green Revolution in drylandareas. The compound growth rate per annum (3.22%) of its productivity (yield/ha) between 1967-68 and 1980-81 iscommendable which surpassed the population growth rate in India. This compound growth rate in productivity progressedfurther @ 1.90 between 1980-81 and 1994-95 over and above the productivity achieved in 1981-82 base year. Theserates have further significance as there had been negative growth rate in area where 5 million ha of its assured rainfalland. deep soil area was diverted to the oilseegs (sunflower, soybean and castor), pulse (greengram) and cotton. Hencewhile strong research base of sorghum could enable enhanced production of II million tonnes from much reduced areaof 12.6 million ha compared with early sixties area of 18 million ha and production of 9 million tonnes, its sparing of 5million ha area to other crops profoundly helped the country to meet its additional requirement of oilseeqs, pulses andcotton and obviously saving of foreign exchange both in terms of less oilseed import and mOre export of cotton.